Inherited or acquired modifiers of iron status may dramatically affect the phenotype in dehydrated hereditary stomatocytosis. (31st August 2018) - Orvain, Corentin; Da Costa, Lydie; Van Wijk, Richard; Pissard, Serge; Picard, Véronique; Mansour‐Hendili, Lamisse; Cunat, Séverine; Giansily‐Blaizot, Muriel; Cartron, Guillaume; Schved, Jean‐François; Aguilar‐Martinez, Patricia
Abstract: Severe iron overload is frequent in dehydrated hereditary stomatocytosis (DHSt) despite well‐compensated hemolysis and no or little transfusion requirement. We investigated 4 patients with proven DHSt, in whom the degree of hemolysis was closely related to iron status. Genetic modifiers increasing iron stores (HFE:pCys282Tyr, HAMP:c‐153C>T mutations) were accompanied with high liver iron concentrations and increased hemolysis, whereas therapeutic phlebotomies alleviated the hemolytic phenotype. There were no manifestations of hemolysis in one patient with low iron stores. Hemolysis reappeared when iron supplementation was given. The search for genetic or acquired modifiers of iron status and the modulation of iron stores may help in the management of these patients.